PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TS-TS) UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN TEKNOLOGI PENGOLAHAN HASIL PERTANIAN (TPHP) KELAS X SMK NEGERI 3 TAKALAR - Saraswati, Saraswati; Rais, Muhammad; Lahming, Lahming (Universitas Negeri Makassar, 2018)
This research is a classroom action research that aims to study and describe the application of type Two stay Two stray (Ts-Ts) coopertative learning model in improving the achievement studient learning outcomes, class X.2 Agricultural Product Processing Technology. The subjects of this study were learner studient of class X.2 TPHP of SMK Negeri 3 takalar totaling 32 the learner studient. Data collection techniques covering observation, written tests and documentation. Data analysis techniques in this study are qualitative analysis to analyze the results of observations and quantitative analysis to analyze learner studient outcomes data using descriptive statistics. The results of this study indicate that the application of the Two stay Two stray (Ts-Ts) type of cooperative learning model can improving the achievement learner studient outcomes, of class X.2 TPHP of SMK 3 Takalar. This matter the based on the value of learner studient outcomes at the stage pre-test, post-test cycle I and post cycle II test that is 1). mastery learner studient on intial test (51,48), learning completeness (18,75), 2). mastery learner studient post test cycle I (65.69), learning completeness (65,62) , 3). mastery learner studient on post test cycle II (79.33), learning completeness (90.62%). This shows that the value of learner studient outcomes of from pre-test, post-test cycle I and post test cycle II has increased.